1994
DOI: 10.1007/bf00714596
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity effects on EMG activity in normal swallow

Abstract: This study investigated the effects of six consistencies on measures of swallow duration, muscle activity, and sound. Electromyographic (EMG) recordings of the submental and infrahyoid muscle complexes, and audio recordings of neck sounds were made while 5 normal subjects swallowed two foods in each of three consistency categories: liquid, thin paste, and thick paste. Total swallow duration, measured from EMG, increased significantly across consistency categories from liquids to thin pastes to thick pastes. Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
119
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(133 citation statements)
references
References 20 publications
12
119
2
Order By: Relevance
“…This result supports the clinical data that was reported that the pharyngeal transit time for dysphagic swallows was longer than for healthy swallows (ClavÉ et al, 2006). However, since thickened fluids have higher yield stresses than unthickened fluids, the individuals still need to generate at least a minimum pressure to propel the bolus through the mouth in the oral space (Reimers-Neils et al, 1994).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This result supports the clinical data that was reported that the pharyngeal transit time for dysphagic swallows was longer than for healthy swallows (ClavÉ et al, 2006). However, since thickened fluids have higher yield stresses than unthickened fluids, the individuals still need to generate at least a minimum pressure to propel the bolus through the mouth in the oral space (Reimers-Neils et al, 1994).…”
Section: Discussionsupporting
confidence: 88%
“…Individuals with dysphagia are known to have lower tongue pressure than healthy individuals, thus increased the transit time in the pharyngeal phase. However, individuals with dysphagia still need to generate enough pressure to propel the bolus through the mouth in the oral phase and for ease of swallowing (how much effort is required to swallow the bolus) (Reimers-Neils et al, 1994). Additionally, in this simplified physical model, it was observed that mass residue was not significantly influenced by the roller estimated pressure which means the mass residue in the pharynx is not dependent on whether the bolus is swallowed by healthy individuals or individuals with dysphagia.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Similarly to a previous study 24 using EMG, the activity of the suprahyoid muscles started at the earliest stage in this study. Subsequently, tongue contact was observed in the anterior region of the palate, followed by the anterior-lateral region and the posterior-lateral region.…”
Section: Order Of Onset Of Emg Activity Of the Suprahyoid Muscles Andsupporting
confidence: 63%
“…Regular fluids require excellent muscle control and accurate timing between the swallowing system and the breathing system. Thickened fluids slow the act of swallowing and by doing so enhance safe swallowing [1]. Understanding the behaviour of these thickened fluids has important clinical implications.…”
Section: Introductionmentioning
confidence: 99%